2015
DOI: 10.1016/j.polymer.2015.08.036
|View full text |Cite
|
Sign up to set email alerts
|

Residual stress relaxation and stiffness in spin-coated polymer films: Characterization by ellipsometry and fluorescence

Abstract: Ellipsometry and fluorescence are used via measurements of film thickness and pyrenyl dye emission spectral shape, respectively, to characterize residual stress relaxation in polystyrene (PS) films. In particular, fluorescence of pyrene-labeled PS (MPy-PS) films, with ~1 mol% pyrene label, provide sensitivity to film stress relaxation and stiffness by the dependence of the ratio of the first to third vibronic peak intensities (I 1 /I 3) of the pyrenyl dye to nanosecondtime-scale molecular caging. Both techniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
64
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 46 publications
(73 citation statements)
references
References 73 publications
9
64
0
Order By: Relevance
“…In agreement with previous dewetting studies to probe residual stress relaxation in thin polystyrene films, Askar et al found Arrhenius temperature dependence of stress relaxation times, having low activation energy comparable to a fast β‐like relaxation process . However, the T g of bulk PS films was unaffected by residual stress relaxation .…”
Section: Fluorescence To Measure Mechanical Responsesupporting
confidence: 88%
See 2 more Smart Citations
“…In agreement with previous dewetting studies to probe residual stress relaxation in thin polystyrene films, Askar et al found Arrhenius temperature dependence of stress relaxation times, having low activation energy comparable to a fast β‐like relaxation process . However, the T g of bulk PS films was unaffected by residual stress relaxation .…”
Section: Fluorescence To Measure Mechanical Responsesupporting
confidence: 88%
“…Although the ratio of the first to third vibronic peak intensities of the pyrenyl dye fluorescence spectra (displayed in Figure a) can be plotted against temperature to give T g (as shown for two different film thicknesses in Figure b), individual isothermal measurements of this ratio were found to be related to a “caging” mechanism involving sequential segmental motion of the polymer . This “caging” was further dependent on the stiffness and residual stress relaxation of the film …”
Section: Fluorescence To Measure Mechanical Responsementioning
confidence: 99%
See 1 more Smart Citation
“…where the values of ͗ u 2 ͘ are determined in the bulk at the bulk T g of the confi ned material and B is an adjustable parameter refl ecting the material's sensitivity to softness of confi nement. The success of ͗ u 2 ͘ as a measure of the softness of confi nement can be understood based upon a general scaling relationship between ͗ u 2 ͘, which is an experimentally accessible [68][69][70][71][72] measure of local segmental rattle space on a picosecond timescale, [ 73,74 ] and the high-frequency shear modulus,…”
Section: What Determines the Magnitude And Direction Of Interface Effmentioning
confidence: 99%
“…The success of ⟨ u 2 ⟩ as a measure of the softness of confinement can be understood based upon a general scaling relationship between ⟨ u 2 ⟩, which is an experimentally accessible measure of local segmental rattle space on a picosecond timescale, and the high‐frequency shear modulus, G kT/(u2) . In essence, this result indicates that the dynamics of near‐interface polymers are more sensitive to interfacial energy when they are confined by a material exhibiting a relatively high glassy modulus.…”
Section: Introductionmentioning
confidence: 99%